2022
DOI: 10.1002/hep.32517
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of ursodeoxycholic acid in patients with acyl‐CoA oxidase 2 (ACOX2) deficiency–associated hypertransaminasemia

Abstract: Background and Aims: A variant (p.Arg225Trp) of peroxisomal acyl-CoA oxidase 2 (ACOX2), involved in bile acid (BA) side-chain shortening, has been associated with unexplained persistent hypertransaminasemia and accumulation of C27-BAs, mainly 3α,7α,12α-trihydroxy-5β-cholestanoic acid (THCA).We aimed to investigate the prevalence of ACOX2 deficiency-associated hypertransaminasemia (ADAH), its response to ursodeoxycholic acid (UDCA), elucidate its pathophysiological mechanism and identify other inborn errors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A more recent study has detected a new mutation and identified several mutations with a potential dysfunctional impact on ACOX2 activity. Moreover, in two patients, the coexistence of two different mutations in heterozygosis but on different alleles also resulted in metabolic disorder leading to C27-BA accumulation [72]. Interestingly, this study revealed that patients with ACOX2 deficiency-associated hypertransaminasemia (ADAH) could benefit from treatment with UDCA, which normalizes serum levels of aminotransferases [72].…”
Section: Acox2mentioning
confidence: 82%
See 1 more Smart Citation
“…A more recent study has detected a new mutation and identified several mutations with a potential dysfunctional impact on ACOX2 activity. Moreover, in two patients, the coexistence of two different mutations in heterozygosis but on different alleles also resulted in metabolic disorder leading to C27-BA accumulation [72]. Interestingly, this study revealed that patients with ACOX2 deficiency-associated hypertransaminasemia (ADAH) could benefit from treatment with UDCA, which normalizes serum levels of aminotransferases [72].…”
Section: Acox2mentioning
confidence: 82%
“…Moreover, in two patients, the coexistence of two different mutations in heterozygosis but on different alleles also resulted in metabolic disorder leading to C27-BA accumulation [72]. Interestingly, this study revealed that patients with ACOX2 deficiency-associated hypertransaminasemia (ADAH) could benefit from treatment with UDCA, which normalizes serum levels of aminotransferases [72]. Two Acox2 knockout mice models have recently been reported.…”
Section: Acox2mentioning
confidence: 86%
“…Thus, the existence of inborn errors in bile acid metabolism leading to the generation of molecular species with unsaturated steroid ring and non-shortened sidechain (C27-bile acids) able to impair hepatocyte function has been described. Inhibition of de novo synthesis with endogenous C24-bile acids together with the hepatoprotective activity of ursodeoxycholic acid (UDCA) could be beneficial in these patients (Figure 2) [118].…”
Section: Inborn Errors Affecting the Expression/function Of Canalicul...mentioning
confidence: 99%
“…In the case of impaired bile secretion due to the accumulation of cholestatic bile acid species, since the secretory machinery is not constitutively impaired but only inhibited, the pharmacological correction of the altered metabolic pathway restores the function. Moreover, intestinal sequestering of endogenous bile acids using resin cholestyramine [119] or dilution of the secreted by treatment with exogenous UDCA [118] have been reported as strategies to reduce the signs of liver damage. Next-generation sequencing has allowed identifying several very infrequent forms of PFIC.…”
Section: Inborn Errors Affecting the Expression/function Of Canalicul...mentioning
confidence: 99%
“…This condition can be accurately identified by a noninvasive diagnostic strategy based on plasma BA profiling, characterized by the predominance of C27-BA intermediates, and ACOX2 sequencing. Ursodeoxycholic acid (UDCA) treatment seems to efficiently attenuate liver damage in these patients [ 29 ]. Whether there is a link between ACOX2 expression and liver inflammation is unknown.…”
Section: Introductionmentioning
confidence: 99%